Motivación y su influencia en el proceso de enseñanza aprendizaje de los estudiantes de bachillerato de la unidad educativa particular “Abdón Calderón” del cantón Quevedo, provincia de los ríos, año 2016 - Ochoa Montiel, Adriana Ángela (2016)
This work reaffirms the importance that has the motivation for the successful development of the classes of English. It is fruit of the pedagogical necessity by one of the authors and must like objective propose routes that motivate to the educational one of English to the best exercise of their educative work, so that this it as well uses that indispensable average motivation as in the design of classes based on the reality of his students. The implementation of a factory with character sets out that they contribute to elevate the degree of interest by the novel thing in the education area and serves as with the professional self-esteem. The author tries to offer a positive alternative to the problematic one detected in the center of application and to optimize therefore the positive attitude of the professors at the time of giving the classes, and therefore, the attitude of the students as opposed to the language.